2010
DOI: 10.1161/strokeaha.110.579219
|View full text |Cite
|
Sign up to set email alerts
|

Childbearing, Child-Rearing, Cardiovascular Risk Factors, and Progression of Carotid Intima-Media Thickness

Abstract: Background and Purpose-Parity is associated with the risk of clinical cardiovascular events and the severity of preclinical atherosclerosis in older subjects. We sought to determine whether childbearing is associated with concurrent changes in cardiovascular risk factors and the progression of carotid intima-media thickness. Methods-We examined the association between the number of children born during a 6-year period and concurrent changes in cardiovascular risk factors and progression of carotid intima-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…It is suggested that the association between childbirth and concurrent changes in IMT may be independent of traditional cardiovascular risk factors (Skilton et al, 2010). However, another study described no association between parity and either IMT or presence of plaques after adjustment for age in a population based cohort of 746 Finnish women (Kharazmi et al, 2007).…”
Section: Wwwintechopencommentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the association between childbirth and concurrent changes in IMT may be independent of traditional cardiovascular risk factors (Skilton et al, 2010). However, another study described no association between parity and either IMT or presence of plaques after adjustment for age in a population based cohort of 746 Finnish women (Kharazmi et al, 2007).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…However, comparisons between men and women distinguish whether the mechanisms for the association between parity and atherosclerosis involve biological processes related to pregnancy or socioeconomic or lifestyle factors that are related to family size and child-rearing. It has been reported that increasing parity is associated with carotid atherosclerosis in women but not in men among a population with at least one risk factor for cardiovascular disease (Lawlor et al, 2003;Skilton et al, 2009;Skilton et al, 2010).…”
Section: Paritymentioning
confidence: 99%
“…The results of our study support these findings, and women should be counseled regarding weight reduction soon after delivery. A study by Skilton et al reported that child bearing augments the atherosclerosis process, thus increasing the risk of CVD [Skilton MR, et al, 2010]. The association between the number of children a woman has and CVD risk can also be explained on the basis of an increase in daily stressors, hassles and financial constraints because of a large family [WHO 2011].…”
Section: Downloaded By [University Of Saskatchewan Library] At 01:41 mentioning
confidence: 99%
“…Some studies have found that people of lower socioeconomic status suffer from the maximum number of CVD risk factors [Capingana DP, et al, 2013;Power C, et al, 2008], whereas others have found no A c c e p t e d M a n u s c r i p t 4 significant association between socioeconomic status and CVD risk factors [Lipowicz A, et al, 2007]. Similarly, some studies have found lifestyle factors to be related to CVD [Hardy R, et al, 2007;Jacobsen BK, et al, 2011], and Skilton et al [Skilton MR, et al, 2010] found increased atherosclerotic changes in carotid intima medial thickness, a subclinical indicator of CVD, to be associated with child-bearing in Australian women.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy might give a rapid progression to atherosclerosis. Skilton et al studied the relationship between parity and carotid atherosclerosis during a 6-year follow-up in a Finnish sample of Cardiovascular Risk in Young Finns Study [134]. They included 1786 subjects, 1005 females and 781 male controls.…”
Section: Late Vascular Disease Associated With Pregnancy Itself and Pmentioning
confidence: 99%